Earthworm Grazed-Trichoderma harzianum Biofortified Spent Mushroom Substrates Modulate Accumulation of Natural Antioxidants and Bio-Fortification of Mineral Nutrients in Tomato - Singh, Udai B.; Malviya, Deepti; Khan, Wasiullah; Singh, Shailendra; Karthikeyan, N.; Imran, Mohd.; Rai, Jai P.; Sarma, B. K.; Manna, M. C.; Chaurasia, Rajan; Sharma, Arun K.; Paul, Diby; et al. (Frontiers in Plant Science, 2018)
The present investigation was aimed at evaluating the impact of earthworm grazed and Trichoderma harzianum biofortified spent mushroom substrate (SMS) on natural antioxidant and nutritional properties of tomato. Results of the investigation reveal that earthworm grazing and Trichoderma harzianum bio-fortification led to significant improvement in the physico-chemical properties of fresh SMS and its application increased the accumulation of natural antioxidants and mineral content in tomato as compared to either T. harzianum biofortified SMS or fresh SMS. In particular, the earthworm grazed, Trichoderma harzianum biofortified SMS (EGTHB-SMS) was found to inhibit lipid peroxidation and protein oxidation with significant increase in total polyphenol and flavonoid content in tomato. Further, it increased Fe2+/Fe3+ chelating activity, superoxide anion radical scavenging activity compared to other treatments. The results thus suggest an augmented elicitation of natural antioxidant properties in tomato treated with (EGTHB-SMS), resulting in a higher radical scavenging activity, that is highly desirable for human health. In addition, the use of SMS to enhance the nutritional value of tomato fruits becomes an environmentally friendly approach in sustainable crop production.